HUBUNGAN INFEKSI SOIL TRANSMITTED HELMINTHS (STH) DENGAN TINGKAT HIGIENITAS PADA MURID SD NEGERI 105296 PERCUT SEI TUAN - ALYA LAILATU ASSZIVA; NURFADLY . (LP2MTBM MAKARIOZ, 2021)
STH infection is an environmental-based disease that is still a health problem for Indonesian people who are transmittedthrough land. This infection generally attacks elementary school age children. This study aims to determine the relationshipof STH infection with the level of hygiene in 105296 elementary school students Percut Sei Tuan. This research is analyticdescriptive with cross sectional approach. The sampling technique is done by a total sampling method with a total sample of190 students. Data processed with chi square test. The results showed that there was a relationship between STH infectionand the level of hygiene in 105296 elementary school students Percut Sei Tuan. With a lack of hygiene level in the PublicElementary School 105296 Percut Sei Tuan as many as 50 people. There is a relationship between STH infection and thelevel of hygiene in 105296 elementary school students Percut Sei Tuan.